When anti-corruption norms lead to undesirable results: learning from the Indonesian experience. - Wibowo, Richo Andi (Crime, Law & Social Change, 2018)
This paper analyzes how and why adverse side-effects have occurred in the implementation of two articles of Indonesia’s anti-corruption law. These articles prohibit unlawful acts which may be detrimental to the finances of the state. Indeed, the lawmakers had good intentions when they drafted the two articles. They wanted to make it easier to convict corrupt individuals by lowering the standard of evidence required to prove criminal liability. The implementation of these articles has raised legal uncertainty. The loose definition of the elements of the crime enables negligence and imperfection of (public) contracts to be considered as corruption. The Constitutional Court has issued two rulings to restrict and guide the interpretation of these articles. However, law enforcement agencies (Supreme Court and public prosecutors) have been unwilling to adhere to the rulings. There are two possible reasons for this. First, as has been argued by several commentators, the law enforcement agencies have misinterpreted the concept of “unlawfulness”. Besides, the law enforcement agencies wish to be seen to be committed to prosecuting and delivering convictions in corruption cases. To do so, they need to maintain looser definitions of the elements of the offence. This paper endorses the Constitutional Court rulings and provides additional reasons in support of their stance. The paper can be considered as a case study for other countries that may be contemplating similar legislation.